Analisis Teoritik Atas Tulisan Geertz Tentang Kyai Jawa Sebagai Cultural Broker - Moch. Muwaffiqillah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This journal article aims to conduct a theoretical analysis of Geertz's article entitled